2016
DOI: 10.1016/j.sjbs.2015.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacokinetics of a proliposome formulation of Ginkgo biloba extract and Ginaton in rats by a sensitive ultra performance liquid chromatography–tandem mass spectrometry method

Abstract: As a novel oral drug delivery system, proliposome was applied to improve the solubility of active components of Ginkgo biloba extract (GbE). There are currently few reports focusing on the pharmacokinetic characteristics of proliposome of GbE (GbP). A rapid and sensitive ultra performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method for the simultaneous quantification of active components of GbP and a commercial tablet product (Ginaton) in rat plasma was developed and successfully validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Ginkgo has been commonly used for anxiety, Alzheimer's disease, and intermittent claudication. It is available in several formulations, including capsules, tablets, and powders (52)(53)(54)(55)(56). A metaanalysis by Weinmann et al showed ginkgo to be more effective than placebo in improving cognition in patients with Alzheimer's disease as well as vascular and mixed dementia (57).…”
Section: Complementary and Alternative Medicine (Cam) Utilization By mentioning
confidence: 99%
“…Ginkgo has been commonly used for anxiety, Alzheimer's disease, and intermittent claudication. It is available in several formulations, including capsules, tablets, and powders (52)(53)(54)(55)(56). A metaanalysis by Weinmann et al showed ginkgo to be more effective than placebo in improving cognition in patients with Alzheimer's disease as well as vascular and mixed dementia (57).…”
Section: Complementary and Alternative Medicine (Cam) Utilization By mentioning
confidence: 99%
“…Currently, ultra‐high‐performance liquid chromatography coupled to quadrupole time‐of‐flight tandem mass spectrometry (UHPLC‐QTOF‐MS/MS) is often applied to identify the chemical compositions in botanicals (Zheng et al, ). However, screening out the target ions from complex compounds rapidly and distinguishing isomers with different positions of the same substituent are very difficult in UHPLC‐QTOF‐MS/MS analysis.…”
Section: Introductionmentioning
confidence: 99%
“…They are also natural antagonists of the platelet‐activating factor receptor (Kurihara, Wardlaw, Moqbel, & Kay, ; Lamant, Mauco, Braquet, Chap, & Douste‐Blazy, ), and show promising effects on neuronal damage and cardiac diseases (Haines et al, ; Smith, Maclennan, & Darlington, ). Conventionally, for the management of cardiovascular diseases, various preparations have been made of G. biloba extracts or ginkgolides, including tablets, capsules and a few injectable forms (Li et al, ; Li, Zhao, & Du, ; Wang et al, ; Woelkart et al, ; Xiao et al, ; Zheng et al, ). As it is currently one of the most widely sold medicinal plants, the global market for ginkgo has been estimated at more than US $700 million.…”
Section: Introductionmentioning
confidence: 99%
“…As ginkgolides are the primary components of G. biloba extracts, pharmacokinetic study of the ginkgolides will greatly facilitate our understanding of the absorption, distribution, transformation and elimination properties and the full profile of these compounds in vivo . Previously, although the pharmacokinetics of Ginkgo terpene lactones have been evaluated in humans, dogs and rats after injection or oral administration of various preparations of the plant extract (Drago, Floriddia, Cro, & Giuffrida, ; Lu et al, ; Lv et al, ; Yan‐Yan, Li‐Li, Guo‐Ming, Rong, & Jing‐Zhen, ), including G. biloba extract preparations (Mauri et al, ; Woelkart et al, ; Xiao et al, ; Zheng et al, ), ginkgolide B (Zhao et al, ) and Ginkgo terpene lactones (Li et al, ; Wang et al, ), neither the effect of food nor the absolute bioavailability of ginkgolides after oral administration has been evaluated in humans or dogs. In this study, the pharmacokinetics and bioavailabilities of ginkgolide A (GA) and ginkgolide B (GB) were profiled in ginkgolide extracts by modification of an established liquid chromatography–tandem mass spectrometry (LC‐MS/MS) assay of the prototype forms of GA and GB (Figure ; Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation